Shake-Table Test of a Strengthened Stone Masonry Building Aggregate with Flexible Diaphragms. Issue 7 (3rd October 2019) - Guerrini, Gabriele; Senaldi, Ilaria; Graziotti, Francesco; Magenes, Guido; Beyer, Katrin; Penna, Andrea
ABSTRACT: A unidirectional shake-table test was performed on the half-scale prototype of a natural stone masonry building aggregate, to investigate the seismic performance of this type of historical construction and to assess the effectiveness of two retrofit solutions. The specimen represented a building aggregate with two adjacent three-storey units, connected along one side as if they were built at different times. Double-leaf stone masonry with undressed blocks and river pebbles was used for the walls. Timber floors constituted flexible diaphragms in their planes. Roofs with different timber truss configurations and heights covered the two units. Improved wall-to-diaphragm connections and tie rods were pre-installed, although initially not fastened, on the prototype. Both retrofit systems were activated after significant damage was reached testing the unstrengthened specimen. This paper describes the seismic behaviour of the prototype, focusing on the effects of the retrofit interventions on damage mechanism evolution, lateral displacement demand, hysteretic response, and dynamic properties degradation.